2011
DOI: 10.1111/j.1440-1746.2011.06808.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori induces promoter hypermethylation and downregulates gene expression of IRX1 transcription factor on human gastric mucosa

Abstract: This study firstly demonstrated that H. pylori infection contributes to IRX1 promoter methylation on gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The remainder was H. pylori infection status was determined based on the rapid urease test as previously described [18]. …”
Section: Methodsmentioning
confidence: 99%
“…The remainder was H. pylori infection status was determined based on the rapid urease test as previously described [18]. …”
Section: Methodsmentioning
confidence: 99%
“…CpG island hypermethylation and genomic DNA hypomethylation are found in gastric tumors and premalignant lesions (Park et al, 2009), and H.pylori infection can induces aberrant CpG island hypermethylation in gastric mucosa (Nakajima et al, 2009;Park et al, 2009). Several reports indicated that accumulation of aberrant methylation in gastric mucosa produces a field for cancerization, and methylation levels correlate with gastric cancer risk (Guo et al, 2011;Wang et al, 2012). However, few studies have investigated the host factors, such as SNPs of DNA methyltransferases (DNMTs) gene, which may affect epigenetic regulation in gastric mucosa (Fan et al, 2010;Wu et al, 2012;Yang et al, 2012).…”
Section: Dnmt3amentioning
confidence: 99%
“…The best-described examples are Helicobacter pylori [33] and uropathogenic Escherichia coli [34] where alterations of methylation profiles are responsible for characteristic changes in host gene expression. Wolbachia infection has also been shown to alter its host epigenetic makeup in a number of recent studies.…”
Section: Introductionmentioning
confidence: 99%